Meta-Analysis: The Effect of Using Digital Physics Teaching Materials on Improving 21st Century Skills - Kurniati, Nia; Sari, Silvi Yulia (PILLAR OF PHYSICS EDUCATION, 2023)
Education is a necessity that cannot be separated from human life. The existence of this education can form a moral and thinking human being. Education in schools/madrasas is expected to be able to build and improve various 21st century skills in accordance with the demands of the industrial revolution 4.0. The 21st century skills, also known as 4C skills, include critical thinking, creativity, communication, and collaboration that learners must master. The solution to improving learners' 21st century skills is the existence of teaching materials that can support learners' 21st century skills in the learning process. Teaching materials that can be used as a solution in facilitating students in accessing learning are teaching materials developed by utilising the advantages of ICT called digital teaching materials, including e-books, e-modules, LKS and other digital teaching materials.  The purpose of this study was to determine the effect size of digital physics teaching materials on improving students' 21st century skills, especially in physics learning. The type of research used is a meta-analysis that analyses 20 national and international articles in the last 4 years (2018-2022). The analysis technique used was to calculate the effect size for each article. The results showed that the meta-analysis study had an effect on digital physics teaching materials to improve 21st century skills based on high school grade level, physics learning materials, types of teaching materials used and 21st century skills achieved. The research findings show that digital physics teaching materials have an effect on improving 21st century skills, especially on critical thinking skills.